Harvest Management Effects on Canopy Height and Light Interception of 'Performer' Switchgrass and its Relationship with Weed Infestation. Issue 3 (1st May 2019) - Bekewe, Perejitei E.; Castillo, Miguel S.; Rivera, R.
Abstract : Defoliation management can determine the presence or absence of desirable forage species. Canopy characteristics and light interception are two critical determinants of productivity and can influence weed pressure. The objectives of this study were to determine the effect of the factorial combination of four defoliation heights (clipped to 10, 20, 30, and 40 cm; DH) and four defoliation frequencies (clipped every 3, 6, 9, and 12 wk; DF) on light interception, canopy height, and weed canopy cover and frequency for 'Performer' ( Panicum virgatum L.) switchgrass and to relate the abovementioned responses to previously reported productivity measurements. The experiment was conducted for 2 yr (2016 and 2017) at the Central Crops Research Station, Clayton, NC. The 16 treatments were allocated in a randomized complete block design replicated four times. Across years, light interception before harvest ranged from ∼45 to 88%, canopy height ranged from 35 to 97 cm, and weed cover and frequency ranged from 0 to 75 and 0 to 95%, respectively. Greater canopy height was associated with greater light interception and lower weed infestation. Weed infestation occurred mainly for treatments harvested every 3 and 6 wk and defoliated to lower stubble heights; however, there was no impact of DH for DF treatments harvested every 9 and 12 wk. Canopy light interception values of at least 70% obtained in our study were associated with defoliation thresholds previously reported in the literature for sustained yields of 'Performer' switchgrass. Switchgrass canopy light interception values of at least 70% were achieved with canopy heights before harvest of ∼60 cm tall.